Kajian Bentuk dan Makna Syair Lagu Tenang Ende Geong Karya Efrem Jaru Manggarai Nusa Tenggara Timur - Dionisius Redemptus Jiri (Universitas Palangka Raya, 2025)
The art of music is a sound that is arranged in such a way that it contains rhythm, song, tone, and harmony, especially from the sound produced by instruments that can produce rhythm. This thesis is titled